The effect of continuous vs. intermittent protocols during small-sided games in soccer on physiological, physical, technical and tactical performance - Rumpf, M. C.; Jäger, J.; Lochmann, M. (Frontiers in Sports and Active Living, 2025)
Small-sided games (SSG) are a common part of the soccer practice and coaching regularly utilize continuous (CSSG) or intermittent games (ISSG). Interestingly, players enjoy the CSSG format to a greater extent, whilst experiencing greater individual perceived exertion (RPE) and higher blood lactate concentration. CSSG reported a decrease in maximal and average heart rate and lower time spent in high heart rate zones (>90% maximum heart rate). Players experienced lower physical strain during CSSG. Variables associated with higher external load such as total distance, total number of sprints, and distances in high-intensity speed thresholds (>14.4 km/h) as well as player load and acceleration variables decreased during CSSG. Little research opposes this idea reporting increased physical demands with the identical variables. The technical performances of players in the two different regimes showed also significant differences. The CSSG reported lower technical engagement (decreased ball involvement, number of dribbling and interceptions). However, yet displaying greater technical efficiency (lower percentage of lost balls, greater percentage successful passes). There is no scientific evidence with regards to tactical differences between the CSSG and ISSG. Depending on the time in the season and the level of players, coaches should favor ISSG promoting greater physical and technical development.